2004
DOI: 10.1523/jneurosci.4352-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Material-Specific Recognition Memory Deficits Elicited by Unilateral Hippocampal Electrical Stimulation

Abstract: Although the medial temporal lobe is thought to be critical for recognition memory (RM), the specific role of the hippocampus in RM remains uncertain. We investigated the effects of transient unilateral hippocampal electrical stimulation (ES), subthreshold for afterdischarge, on delayed item RM in epilepsy patients implanted with bilateral hippocampal depth electrodes. RM was assessed using a novel computer-controlled test paradigm in which ES to left or right hippocampus was either absent (baseline) or synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
71
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 49 publications
10
71
1
Order By: Relevance
“…Standardized neuropsychological examination in our study, however, revealed mildly or moderately impaired verbal long-term memory in patients with left HI, and nonverbal long-term memory deficits in patients with right HI. These memory deficits are in line with other temporal lobe pathologies, as described by lesional studies, 20 functional studies with transient unilateral hippocampal electric stimulation in epilepsy patients, 21 or functional MRI studies. 22 These are cognitive areas that may well escape a standard neurological examination in acute stroke patients, which focuses on the most common items defined in the NIH stroke scale.…”
Section: Discussionsupporting
confidence: 84%
“…Standardized neuropsychological examination in our study, however, revealed mildly or moderately impaired verbal long-term memory in patients with left HI, and nonverbal long-term memory deficits in patients with right HI. These memory deficits are in line with other temporal lobe pathologies, as described by lesional studies, 20 functional studies with transient unilateral hippocampal electric stimulation in epilepsy patients, 21 or functional MRI studies. 22 These are cognitive areas that may well escape a standard neurological examination in acute stroke patients, which focuses on the most common items defined in the NIH stroke scale.…”
Section: Discussionsupporting
confidence: 84%
“…Sobotka et al (2005) also showed recently that delay-interval ES directly in the monkey hippocampus, persisting for 125-250 ms but delivered 1 s after onset of the sample stimulus, disrupts recognition in a short-term delayed matching-to-sample task. Their findings, in conjunction with our own and those of Coleshill et al (2004), suggest that the hippocampus may be differentially engaged, or controlled, in long-term versus short-term (working) memory tasks.…”
Section: Discussionsupporting
confidence: 67%
“…Impairments to subsequent recognition ability attributable to disruption of hippocampal encoding activity have been reported in a recent experiment by Coleshill et al (2004) that used subepileptogenic electrical stimulation (ES) applied directly to the hippocampus in human epilepsy patients. ES was time locked to the presentation of visual stimuli during the encoding phase of a recognition memory task similar to the one we used in the present experiments, resulting in recognition impairments for such items compared with items presented for encoding without concurrent ES.…”
Section: Discussionmentioning
confidence: 99%
“…The two studies that showed significant effects of the hippocampal stimulation on memory encoding (at least p < .01; Coleshill et al, 2004 andLacruz et al, 2010) also did not show complete memory disruption (patients' performance were not consistently at chance levels across all stimulation trials). One explanation for these counterintuitive findings is that given that the hippocampus is a large structure, stimulation delivered to one part of it would not have striking effects on memory as hippocampal lesions do.…”
Section: Hypothalamic Stimulationmentioning
confidence: 93%
“…We discuss six aDES studies on memory modulation which provide a useful framework for considering the varying effects of hippocampal stimulation on memory performance (Coleshill et al, 2004;Fell et al, 2013;Koubeissi, Kahriman, Syed, Miller, & Durand, 2013;Lacruz et al, 2010;Miller et al, 2015;Suthana et al, 2012). These studies all used depth electrodes targeting the hippocampus, parahippocampal cortex, or fornix.…”
mentioning
confidence: 99%